Qiyusanlong Formula Induces Autophagy in Non-Small-Cell Lung Cancer Cells and Xenografts through the mTOR Signaling Pathway. (22nd May 2021) - Gao, Yating; Wang, Xinheng; Yang, Qinjun; Wang, Xiaole; Zhang, Xingxing; Tong, Jiabing; Yang, Cheng; Wu, Di; Li, Zegeng
Abstract : Objective . Qiyusanlong (QYSL) formula has been used in the clinic for more than 20 years and has been proved to have pronounced efficacy in the treatment of non-small-cell lung cancer (NSCLC). This work aims to evaluate the molecular mechanism of QYSL formula action on NSCLC, specifically in relation to autophagy induction. Methods . In vitro, CCK-8 was used to detect the effect of QYSL serum on cell viability in A549 cells. In vivo, A549 cells were implanted subcutaneously in nude mice to establish a xenograft model. TUNEL staining was used to measure cell apoptosis and TEM to observe the autophagy-related morphological changes in vitro and in vivo. Western blotting, RT-qPCR, and immunofluorescence were used to measure autophagy-related proteins. In addition, rapamycin (an inhibitor of mTOR and inducer of autophagy) and MHY1485 (an activator of mTOR and inhibitor of autophagy) were used to determine whether QYSL-induced autophagy was regulated by the mTOR pathway. Results . QYSL serum inhibited the cell viability of A549 cells in a concentration‐dependent manner. In vivo, the QYSL formula inhibited xenograft growth. The QYSL formula promoted apoptosis in A549 cells and induced autophagosome formation in vitro and in vivo. In addition, the QYSL formula downregulated the expression of mTOR and p62, while it upregulated the expression of ATG-7 and Beclin-1 and increased the LC3-II/LC3-I ratio. QYSL serum inhibited p-mTOR in a similar manner to rapamycin while reducing the activating effects of MHY1485 on p-mTOR. Conclusion . The QYSL formula has anti-lung cancer effects and promotes autophagy through the mTOR signaling pathway.